Examination of stress–turnover relationship through perceived employee's exploitation at workplace - Mohd Abass Bhat; Shagufta Tariq; Riyaz Ahmad Rainayee (PSU Research Review, 2024)
Purpose – In the purview of stress–turnover relationship, the present study aims to explore the endogenous and exogenous aspects of stress and employees' turnover intentions. Further, it also intends to evaluate the mediating role of perceived employee's exploitation between stressors and employee turnover intentions. For that matter, antecedents of stressors were identified and classified into endogenous and exogenous stressors: endogenous stressors relate to the employees' negative psychological contact within an organization and exogenous stressors are various macro-economic factors which have a considerable influence on employees' workplace behavior. Design/methodology/approach – For the purpose of this study, this study choses private school teachers as respondents working in the economically depressed state of India. Thus, data for the present study has been collected from 628 private school teachers of J&K (India) which were randomly selected. In order to ensure valid and reliable statistical inferences from the study, data collected has been validated using confirmatory factor analysis and hypothesis testing has been carried out through structural equation modeling. Findings – It was found that both types of stressors were contributing negatively toward employee's psychological state resulting in undesirable employee organizational relationships manifested as turnover intentions among employees. Moreover, perceived employee's exploitation was found to intensify the relationship of employee turnover as a dependent variable regressed on endogenous, exogenous and occupational stress by fully mediating the stress–turnover intricacies. Research limitations/implications – The implications of the study include the identification of employees' stressor needs in order to gauge the understanding of the mechanism by which employees react to their environment and develop attitudes toward their jobs. The present study includes a small sample size obtained from private educational institutions only. Therefore, there is a need to take a geographically diverse sample that is inevitable for universal inferences and validity. Originality/value – Very little research has been conducted to explore endogenous, exogenous and unique stressors such as economic stress and perceived external opportunities which constitute the overall stress. Moreover, to the best of the authors’ knowledge, this is the first study which tests the model empirically that examines the effect of stress–turnover relationship through perceived employee's exploitation in the teaching and educational sector.